MENINGKATKAN KEMAMPUAN MENULIS TEKS ULASAN CERPEN MENGGUNAKAN TEKNIK BRAINWRITING PADA SISWA KELAS VIII SMP NEGERI 8 WASILE - Kristin Senen; Sarmina Ati (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
This study aims to improve the ability to write short story review texts in class VIII students of SMP Negeri 8 Wasile. by applying the brainwriting technique. The research model used is Classroom Action Research (CAR). The data analysis technique was carried out using quantitative description techniques. The results of the study show that. First, improving the brainwriting technique can improve the quality of the learning process of writing short story review texts. There is an improvement in the process in the aspects of learning situations, student focus, and activeness, making positive changes so that learning to write short story review texts is more interesting and enjoyable. Second, learning to write short story review texts with the brainwriting technique approach can improve the results of short story review text writing skills in the Action cycle I with a score of 80% in the Good category while in the action cycle II with a score of 100% in the Very Good category. Overall at the end of cycle II all aspects and criteria for writing short story review texts experienced a significant increase. Based on the results of the study above, it is known that the use of the brainwriting technique approach is successful and can improve the writing skills of short story review texts of class VIII students of SMP Negeri 8 Wasile